The Impact of Withering Pre-Processing and Distillation Durations on Yield and Quality of Citronella Oil - Ahmad, Usman; Dentaka, Dentaka; Krah, Courage Y. (Green Engineering Society, 2025)
The global essential oil market is expanding rapidly, driven by demand from the pharmaceutical, cosmetic, and food industries. This has positioned Indonesia as a key producer and exporter of citronella essential. However, inconsistent processing methods lead to variable quality and suboptimal oil yields. This study addresses this gap by investigating how withering duration (0-72 hours) and distillation time (2-4 hours) affect yield and quality of distilled oil from Cymbopogon nardus (Mahapengiri variety). The results show that the highest oil yield (1.14%) was achieved with 72 hours of withering followed by 4 hours of distillation, demonstrating that prolonged withering significantly enhances extraction efficiency by reducing moisture content and facilitating oil release from plant cells. Quality assessments revealed that extended processing improved key physical parameters, including density (0.8897 g/cm³) and refractive index (1.4694), which conformed to Indonesian export standards (SNI 06-3953-1995). Chemical analysis using gas chromatography-mass spectrometry (GC-MS) indicated that optimal processing conditions increased the concentrations of citronellal (43.24%) and geraniol (21.73%), critical compounds that enhance the oil’s market value. However, longer distillation times also intensified the oil’s color, shifting it from clear to a deep yellow, which may influence consumer preference despite meeting industry chromatic standards. The study highlights the trade-offs between yield, quality, and visual characteristics in citronella oil production. These findings provide actionable insights for Indonesian producers aiming to optimize post-harvest techniques and improve the competitiveness of citronella oil in global markets.